Keragaman ikan karang di perairan Pulau Makian Provinsi Maluku Utara - Najamuddin N; Samar Ishak; Adityawan Ahmad (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of the present study was to identify and evaluate reef fish community structure at Makian Island. Sampling was conducted in two stations at coordinate position of 00º.22’15.75”N -127 º.25’12.00”E to 00 º.22’7.90”N - 127º. 25’17.40”E with two different depths i.e. 5 meters and 10 meters. Coral reef data were collected using line intercept transect method, while the reef fish data were taken using a census visual method. A total of 138 species of coral reef fishes were recorded during the survey belong to 47 genera and 21 families. The fish diversity on station 1 for both depths (5 meters and 10 meters) were a medium level, while on station 2 at 5 meters water depth was also a medium category, but a higher diversity was detected at 10 meters depth. The percentage coral covers on station 1 at 5 meters depth was a medium level, at 10 meters depth was classified as high covered, while on station 2 at 5 meters and 10 meters depth were classified very high percent covers.Key word. Diversity, coral, percent covers, and line intercept transect